2021
DOI: 10.1002/aqc.3563
|View full text |Cite
|
Sign up to set email alerts
|

It is the ambience, not the menu. Prey availability does not drive habitat selection by the endangered Pyrenean desman

Abstract: 1. The Pyrenean desman (Galemys pyrenaicus) is an endangered stream-dwelling insectivore endemic to the Iberian Peninsula and the north of the Pyrenees. It favours riffles over slow habitats such as runs or pools, yet it is still unclear whether habitat preference is based on prey availability or on other factors, such as mechanical constraints on its hunting habits. 2. Desman diet and prey selection were analysed along the pristine Elama Stream and the slightly modified Leitzaran Stream in the Basque Country,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 42 publications
(82 reference statements)
2
22
0
Order By: Relevance
“…Both mammals avoided the soft-bodied taxa that inhabit fine sediments (e.g. Athericidae, Limoniidae and Oligochaeta), a finding also reported in other studies of G. pyrenaicus (Esnaola et al 2021). This situation illustrates the interspecific trophic competition occurring between G. pyrenaicus and the other analysed semi-aquatic predators, as well as the partial prey overlap, in which these predators coexist by frequenting a different microhabitat determined by their specific morphological and physiological adaptations (Castién and Gosálbez 1999;Churchfield and Rychlik 2006).…”
Section: Trophic Ecology and Diet Specialisation In G Pyrenaicussupporting
confidence: 83%
See 4 more Smart Citations
“…Both mammals avoided the soft-bodied taxa that inhabit fine sediments (e.g. Athericidae, Limoniidae and Oligochaeta), a finding also reported in other studies of G. pyrenaicus (Esnaola et al 2021). This situation illustrates the interspecific trophic competition occurring between G. pyrenaicus and the other analysed semi-aquatic predators, as well as the partial prey overlap, in which these predators coexist by frequenting a different microhabitat determined by their specific morphological and physiological adaptations (Castién and Gosálbez 1999;Churchfield and Rychlik 2006).…”
Section: Trophic Ecology and Diet Specialisation In G Pyrenaicussupporting
confidence: 83%
“…In this aquatic environment, the Pyrenean desman outcompetes both N. fodiens and C. cinclus. Although its avoidance of terrestrial prey observed in the Catllar stream matches other studies that have used a morphological approach for prey identification (Santamarina 1993;Bertrand, 1994;Castién and Gosálbez 1999), some studies based on a genetic approach (Biffi et al 2017a, b;Esnaola et al 2021) indicate that the desman actively consumes terrestrial groups. Both these approaches permit the identification of a wide range of prey items but it is, nevertheless, important to understand the biology of these prey species when assessing their use as food resources to avoid misleading interpretations.…”
Section: Trophic Ecology and Diet Specialisation In G Pyrenaicussupporting
confidence: 64%
See 3 more Smart Citations